Social change - Weinstein, Jay A. (Rawat Publications, 2011)
This introduction to social change covers the momentous and relatively recent changes that have occurred in the human condition, balancing theory with observation and incorporating comparative global examples throughout. The third edition of Social Change has been thoroughly updated and revised, including a new discussion of the current economic crisis and the interconnectedness of the global economy, new empirical data on globalization, and updated discussions of evolution and altruis